Production and PFM characterization of barium titanate nanofibers - Sá, Pedro (2012)
Continuous nanofibers of barium titanate (BaTiO3) with average diameter of 150–300 nm have been produced by means of mutual sol-gel and electrospinning routines with subsequent calcination step. The structural characterization of the obtained nanofibers has been performed by XRD and Raman spectroscopy. Their individual grain and domain structures were studied by piezoresponse force microscopy (PFM). The results show that the fibers consist of stacked tetragonal ferroelectric BaTiO3 grains with average size of about 50–100 nm and random initial orientations. The piezoelectric response is similar to that obtained for domain model in ferroelectric tetragonal perovskites.